The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/tox.22316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a glyphosate‐based herbicide on the uterus of adult ovariectomized rats

Abstract: Glyphosate is the active ingredient of several herbicide formulations. Different reports suggest that glyphosate-based herbicides (GBHs) may act as endocrine disruptors. We evaluated the potential estrogenic effects of a GBH formulation using the uterotrophic assay. Adult ovariectomized rats were sc injected for 3 consecutive days with: saline solution (vehicle control), 2.10 g E /kg/day (uterotrophic dose; UE ), 2.10 g E /kg/day (nonuterotrophic dose; NUE ), or 0.5, 5, or 50 mg GBH/kg/day of the. Twenty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 47 publications
(67 reference statements)
3
16
0
Order By: Relevance
“…On the contrary, other studies showed that glyphosate (the active ingredient of formulations) promotes cell proliferation in hormone-dependent breast cancer cells by activating the ESR1 (Thongprakaisang et al 2013, Mesnage et al 2017. Similarly, we and other authors have shown that glyphosate and GBHs can modulate the expression of both ER subtypes in the rat uterus (Varayoud et al 2017) as well as induce ESR1 and ESR2 protein expression in T47D breast cancer cells (Thongprakaisang et al 2013). In the present study, we observed that postnatal exposure to GBH enhanced ESR1 and ESR2 expression in the rat uterus after E2 treatment.…”
Section: Loss Of Ctnnb1 Expression On the Cell Surface Destabilizes Asupporting
confidence: 71%
“…On the contrary, other studies showed that glyphosate (the active ingredient of formulations) promotes cell proliferation in hormone-dependent breast cancer cells by activating the ESR1 (Thongprakaisang et al 2013, Mesnage et al 2017. Similarly, we and other authors have shown that glyphosate and GBHs can modulate the expression of both ER subtypes in the rat uterus (Varayoud et al 2017) as well as induce ESR1 and ESR2 protein expression in T47D breast cancer cells (Thongprakaisang et al 2013). In the present study, we observed that postnatal exposure to GBH enhanced ESR1 and ESR2 expression in the rat uterus after E2 treatment.…”
Section: Loss Of Ctnnb1 Expression On the Cell Surface Destabilizes Asupporting
confidence: 71%
“…cyminum essential oil at dose levels of 250,500 and 1000 mg/ day was orally administered to female mice for 14 days caused marked elevation in the body weight , uterus and estradiol levels(p<0.001) whereas the progesterone levels were decreased significantly in all dose groups including 25 mg/kg after 28 days study (p=0.001) . Phytoestrogen properties of cumin extract has been previously described (25)and it was identified useful in treating postmenopausal osteoporosis and estrogen-related disorders in bilaterally ovariectomized rat as an osteoprotective product comparable with estradiol (26).This study suggests the phyotoestrogenic effects of cumin essential oil which should be confirmed by later studies using specific models. On the other side, another study showed a marked reduction in sperm density in the cauda epididymis and testes and sperm motility in the cauda epididymis as well as fertility reduction, significant decreases in the number of testicular cells, secondary spermatocytes and round spermatids (27) with its endocrine disruptive effects.…”
Section: Discussionsupporting
confidence: 61%
“…caused a testosterone-disruptor effect (Romano et al, 2012). In addition, nephrotoxicity (Hamdaoui et al, 2016), hepatotoxicity (ElShenawy, 2009;Haskovic et al, 2016;Tang et al, 2017;Lozano et al, 2018), neurotoxicity on dopaminergic markers (Hernández-Plata et al, 2015;Martínez et al, 2018), and on the immature rat hippocampus (Cattani et al, 2014), effects on intestine peristalsis (Chłopecka et al, 2014(Chłopecka et al, , 2017, sperm quality (Abarikwu et al, 2015;Dai et al, 2016) and reproductive toxicity (Owagboriaye et al, 2017), estrogenic effects (Vandenberg et al, 2012;Varayoud et al, 2017) and the effect of neonatal exposure to female adult reproductive performance (Ingaramo et al, 2016 have been demonstrated. Liver dysfunction observed in rats correlated with gut microbiome disturbances identified in a recent study : longterm effects of Roundup Grand Travaux Plus R at 3 doses (corresponding to glyphosate concentrations of 50 ng/l, 100 µg/l, and 2.25 g/l) on the gut microbiota in Sprague-Dawley rats were observed by determining 141 bacteria families by highthroughput sequencing, of which alteration of the Firmicutes to Bacteroidetes ratio was recorded at different levels in females (but not in males).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Repeated 4-week intranasal administration of Glifoglex R in male CF-1 mice (∼2 mg/nostrils/day) affected the central nervous system (probably by altering neurotransmission pathways), caused neurobehavioral effects (by decreasing the ambulatory activity and increase in thigmotaxis, indicating higher anxiety levels), and impaired recognition memory as early as after 6 h (Baier et al, 2017). Results on hormonal effects of glyphosate-based herbicides on rats indicate modulation of the expression of estrogen-sensitive genes in the exposed animals with non-monotonic dose-response curves , indicating the need for hazard-based considerations in risk assessment (Vandenberg et al, 2012;Varayoud et al, 2017). A recent meta-analysis of eight previous studies on reproductive toxicity on males, carried out between 1992 and 2016, on sperm counts in rodents (Kunming and B6C3F mice and Sprague Dawley, Wistar and Fischer F344 rats) upon glyphosate administration at 40-50,000 mg/kg resulted in decreased sperm concentrations showing that glyphosatebased herbicides exerts reprotoxicity to male rodents.…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%